2020
DOI: 10.1038/s41598-020-57748-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Discriminatory Performance of Different Well-Known Risk Assessment Scores for Extended Hepatectomy

Abstract: The aim of this study was to assess and compare the discriminatory performance of well-known risk assessment scores in predicting mortality risk after extended hepatectomy (EH). A series of 250 patients who underwent EH (≥5 segments resection) were evaluated. Aspartate aminotransferase-to-platelet ratio index (APRI), albumin to bilirubin (ALBI) grade, predictive score developed by Breitenstein et al., liver fibrosis (FIB-4) index, and Heidelberg reference lines charting were used to compute cutoff values, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A large number of studies have shown that the ALBI score has a good predictive effect on PHLF [11][12][13][14][15]. The ALBI score also showed a good predictive effect in survival and treatment effect of patients with HCC [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the ALBI score has a good predictive effect on PHLF [11][12][13][14][15]. The ALBI score also showed a good predictive effect in survival and treatment effect of patients with HCC [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other prominent scores, such as the recently validated MEGNA score, the RSI does not require postoperative data (e.g., histopathological staging) and thus can be of value not only for post- but also for preoperative therapeutic decision-making [ 14 ]. Of note, further well-known risk assessment scores, such as the FIB-4, ALBI, or Heidelberg score, were not further evaluated in the current study due to a lack of consistent preoperative monitoring of all required variables [ 33 ].…”
Section: Discussionmentioning
confidence: 99%